Hemoglobin Switching During Murine Embryonic Development - Wong, Man-Chun Peter (My University, 1982)
Around day 8 of mouse embryonic development, yolk sac produces circulating nucleated erythroblasts synthesizing primarily embryonic hemoglobins (Hb E). By day 12 of gestation, fetal liver releases nonnucleated erythrocytes containing adult hemoglobins (Hb A). The objective herein was to examine the cellular mechanism of hemoglobin ontogeny during mouse embryonic development.
Embryonic peripheral blood cells from 9-12 day embryos were cultured in either plasma clot or methylcellulose for 6-8 days. Pokeweed mitogen stimulated adult spleen cell conditioned medium (SCM) either with or without erythropoietin (Epo) was added to these cultures. Large erythroid colonies were observed by the sixth day of culture. In another type of experiment embryonic fluid was obtained from exocelomic cavity of day 10 embryos and was added to these cultures with Epo, but without SCM. Erythroid colonies were also observed. In some other experiments, cultures of yolk sac cells from 9 - 10 day embryos with SCM, with or without Epo also gave rise to large erythroid colonies after 6 - 8 days in vitro. Furthermore, such colonies were also detected when fetal hepatic cells of 11 - 13 day embryos were cultured with SCM with or without Epo. Hemoglobin synthesis was analysed by various techniques, i.e., electrophoresis, isoelectric focusing and ion-exchange chromatography. In all cultures, only Hb A synthesis could be detected, although the experiments do not rule out the possibility that minute amount of embryonic hemoglobins were present.
In another series of experiments, fragments of embryonic tissues from day 8 embryos were cultured for 6-8 days in methylcellulose with Epo and/or SCM. Hemoglobin present in cultures was examined by the sensitive isoelectric focusing microassay. Cultures of early day 8 tissues produce only Hb E. Cultures of late day 8 embryonic tissues with Epo alone produce primarily Hb E with some Hb A as well. Similar cultures with both Epo and SCM produce both Hb E and Hb A, and the proportion of Hb A synthesized is considerably higher. Cultures of day 10 tissues in the presence of both Epo and SCM produce only adult hemoglobins.
These results suggest the following model for the development of murine embryonic erythropoiesis: Hemopoietic progenitor cells capable of giving rise to erythroblasts synthesizing Hb E occur early in embryonic development. This is followed shortly by the appearance of erythroid progenitor cells committed to produce erythroblast progeny synthesizing Hb A. The latter progenitor cells are present in circulation. They seed fetal liver and initiate fetal hepatic erythropoiesis.
Keywords: Medical Sciences; Medical Sciences